STRATEGI DAKWAH PERSPEKTIF INFORMAL POPULER (TELAAH DAKWAH KH. A SHOHIBUL WAFA TAJUL ARIFIN) - Misbach, Irwan (Jurnal Dakwah Tabligh, 2018)
The problems faced by the ummah always differ both qualitatively and quantitatively. However, these people’s problems need to be identified and sought for relevant and strategic solution solutions through da’wah strategy which includes systematic, smart, and professional method, approach, and technical preaching. Abah Anom as kyai or figure who has a strategic and central position in society and as self-educated. With his position, then he can provide Islamic religious knowledge to the pesantren community as a traditional educational institution which is a means to transfer knowledge to the community as an informal leader. Abah Anom’s strategy of preaching emphasizes the method of dhikrullah (remembering Allah). It is based on the word of Allah swt, that the Qur’an can be a medicine.